Studi kompatibilitas antara rootstock dan scion jati (tectona grandis l.f.) pada metode side grafting dan buds grafting=Study of Compatibility between Rootstock and Scion Teak (Tectona grandis L.f.) on Both Side ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The commercial vegetative propagation of forestry program has recently became more popular. Vegetative propagation, as a part of regenerative method, would become the standard method of regeneration of many species that currently propagated by seedling, included teak (T. grandis), a group of Seasonal Tropical Forest plants which produced economically a high value of wood. Besides successful grafting, there was a problem of incompatibility of grafting in its growth between rootstock and scion. This research was to know the best compatibility between rootstock and scion regarding grafting method and also to know the influence between side-grafting and buds-grafting method for getting grafting compatibility. The method was used factorial split-split plot design which based by Randomized Completely Design. The first factor was five rootstocks as a main plot, the second factor was five scion clones, then the third factor was two grafting methods that repeated in three blocks. The result of this research showed that there was a variation of significant grafting compatibility among rootstock, scion and grafting method. Nevertheless, for getting the best compatibility between rootstock and scion needed the combination of the rootstock of Pengkol Jati Ayu Karangmojo and scion of Marga Sari. A successful percentage value of its lifetime was 86.67%, 22.65 centimeter in height, 5.27 millimeter in diameter, 4.29 in strong, and number of leaves were 9.37. Side-grafting method of this research had given the better growth than the buds-grafting method. Side-grafting method in percentage of lifetime was 62.13 %, 18.58 centimeter in height, 5.13 millimeter in diameter, 3.33 cm/ mm in strength of seedling and number of leaves were 9.03.